Polymers containing amino bis(methylene phosphonic acid) groups for scale inhibition - Köken, Nesrin (Emerald, 2019)
Purpose The purpose of this paper is to prepare poly[allyl amino bis(methylene phosphonic acid)-ran-acrylic acid]s by two different routes. In the first route, poly(allyl amine-ran-acrylic acid)s were produced by radical copolymerization of a mixture of ally amine and acrylic acid, then converted into poly[allyl amino bis(methylene phosphonic acid)-ran-acrylic acid]s by the Mannich reaction with a mixture of formaldehyde and phosphonic acid. In the second route, allyl amino bis(methylene phosphonic acid) monomer was synthesized and copolymerised with acrylic acid. The aim of this work is to produce low-molecular-weight copolymer with the low amount of nitrogen and phosphorous having better scale inhibiting performance than commercial low-molecular-weight poly(acrylic acid)s. Design/methodology/approach Poly(allyl amine-ran-acrylic acid)s were prepared by radical copolymerisation of a mixture of ally amine and acrylic acid, and the molecular weight of copolymers was regulated by using an effective chain transfer compound and the formed copolymer was reacted with a mixture of formaldehyde and phosphorous acid. Allyl amino bis(methylene phosphonic acid) monomer was prepared and then copolymerised with acrylic acid using radical initiators. Findings Poly[allyl amino bis(methylene phosphonic acid)-ran-acrylic acid] produced with both routes, especially low-molecular weight ones have better anti-scaling performance than low-molecular-weight commercial poly(acrylic acid). Research limitations/implications By using an excess of formaldehyde and phosphonic acid, a limited increase in the conversion of amine groups of poly(allyl amine-ran-acrylic acid) to amino methylene phosphonic acid groups was achieved, so unreacted amine groups were always present in the structure of the final copolymers. Practical implications The low-molecular-weight poly[allyl amino bis(methylene phosphonic acid)-ran-acrylic acid] may be used as a better anti-scaling polymer in industry. Social implications The low-molecular-weight poly[allyl amino bis(methylene phosphonic acid)-ran-acrylic acid] is an alternative polymer for scale inhibition in the water boilers. Originality/value The low-molecular-weight poly[allyl amino bis(methylene phosphonic acid)-ran-acrylic acid] copolymers containing both carboxylic acid and amino bis(methylene phosphonic acid) are more effective anti-scaling additives than poly(acrylic acid)s in water boilers.